2016
DOI: 10.1371/journal.pone.0166107
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Lineage Dynamics of Human Influenza B Viruses

Abstract: The prediction of the lineage dynamics of influenza B viruses for the next season is one of the largest obstacles for constructing an appropriate influenza trivalent vaccine. Seasonal fluctuation of transmissibility and epidemiological interference between the two major influenza B lineages make the lineage dynamics complicated. Here we construct a parsimonious model describing the lineage dynamics while taking into account seasonal fluctuation of transmissibility and epidemiological interference. Using this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Vijaykrishna and colleagues suggested that the observed differential age distribution may be explained by either the higher effective reproductive number of B/Victoria; a broader response against B/Victoria viruses in older people; and/or differences in the prevalence of receptor binding molecules that help B/Victoria and B/Yamagata viruses infect respiratory tract cells in young children and adults [40]. Another hypothesis is that the bimodal age distribution of B/Yamagata cases may be the result of a shorter duration of acquired immunity developed after infection with B/Yamagata vs. B/Victoria viruses [41]. Finally, antigenic original sin (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Vijaykrishna and colleagues suggested that the observed differential age distribution may be explained by either the higher effective reproductive number of B/Victoria; a broader response against B/Victoria viruses in older people; and/or differences in the prevalence of receptor binding molecules that help B/Victoria and B/Yamagata viruses infect respiratory tract cells in young children and adults [40]. Another hypothesis is that the bimodal age distribution of B/Yamagata cases may be the result of a shorter duration of acquired immunity developed after infection with B/Yamagata vs. B/Victoria viruses [41]. Finally, antigenic original sin (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Nagy et al [30] found eligible simulations during their calibration process for durations of naturally acquired immunity against influenza B ranging between 0.5 and 75 years. A recent dynamic modeling study from Japan [59], however, estimated much shorter durations of natural immunity against influenza B than the above mentioned studies, estimating 1.15 years for B/Vic and only 0.08 years for B/Yam, although this does not align well with current knowledge on the relatively conserved antigenic nature of influenza B [60]. For the duration of vaccine-induced protection, a recent study by Kissling et al [57] suggested that protection against influenza B was longer than that against influenza A/H3N2, possibly due to a more rapid antigenic drift of A/H3N2 [61].…”
Section: Expert Commentarymentioning
confidence: 99%
“…The use of weekly case counts, an interval comprising more than two generation times, may lead to some bias in the estimation of the growth rate and thus R e , although this bias was estimated at 5% for six-day time aggregation for the epidemic growth method, with a generation time function and reproduction number similar to our study ( Obadia et al, 2012 ). Epidemic dynamics may vary by influenza A subtype and B lineage ( Kwok et al, 2017 ;Nyirenda et al, 2016 ;Xu et al, 2015 ;Yang et al, 2018aYang et al, , 2018b ), but we were unable to estimate R e by subtype or lineage because the information is in-complete for many countries in FluNet. FluNet data are sourced from only one or a few WHO-certified influenza centers located in major cities in each country ( WHO, 2020 ) and so, our findings may be more representative of epidemic dynamics in populations of major cities.…”
Section: Discussionmentioning
confidence: 68%